ہندو مذہبی متون اور عسکری تصورات: تاریخی و معاصر تناظر میں ایک تفصیلی تحقیقی مطالعہ: HINDU RELIGIOUS TEXTS AND MILITARY CONCEPTS: A DETAILED HISTORICAL AND CONTEMPORARY ANALYTICAL STUDY (Al-Aasar, 2026)
This research article explores the military and political ideas found in Hindu religious texts and historical traditions. The study focuses on important Hindu scriptures such as Manu Dharma Shastra, Bhagavad Gita, Ramayana, and Mahabharata, which contain discussions about war, duty, kingship, power, and social order. The article explains how these texts influenced the social and political structure of Hindu society, especially through the concepts of caste system and the role of the warrior class.The research also examines the development of Hindu nationalism in the modern period and discusses organizations such as RSS and Bajrang Dal. In addition, the study highlights issues related to religious minorities, communal violence, and the Kashmir conflict in the context of modern India.This research uses a historical and analytical method to understand the connection between religion, politics, and militarism in Hindu tradition. The study concludes that Hindu religious and historical literature includes strong ideas related to warfare, authority, and state power, which have continued to influence social and political movements in South Asia. At the same time, the study emphasizes the importance of balanced and objective academic analysis while discussing religious traditions and historical events.